The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11751-015-0220-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of soft-tissue traction forces in bone segment transport for callus distraction

Abstract: Callus distraction using bone segment transport systems is an applied process in the treatment of bone defects. However, complications such as muscle contractures, axial deviation and pin track infections occur in the treatment process using the currently available devices. Since successful treatment is influenced by the applied distraction force, knowledge of the biomechanical properties of the involved soft tissues is essential to improve clinical outcome and treatment strategies. To date, little data on dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…From ex vivo approaches, a large number of existing studies in the literature have examined these changes by analyzing samples harvested after the slaughter of their specimens. 5,13,16,18,20,21,27,28,44 Muscles tend to adapt to limb elongation due to the lengthening of their fibers and the addition of new sarcomeres under a slight extension. 30,35 However, excessive elongation (> 30% of the initial length) could trigger important histological changes, and a reduction of ST stiffness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From ex vivo approaches, a large number of existing studies in the literature have examined these changes by analyzing samples harvested after the slaughter of their specimens. 5,13,16,18,20,21,27,28,44 Muscles tend to adapt to limb elongation due to the lengthening of their fibers and the addition of new sarcomeres under a slight extension. 30,35 However, excessive elongation (> 30% of the initial length) could trigger important histological changes, and a reduction of ST stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…30,35 However, excessive elongation (> 30% of the initial length) could trigger important histological changes, and a reduction of ST stiffness. 27 Tendons and ligaments present a lower capacity to adapt to bone lengthening than muscles, 5 and also suffer an important reduction in their mechanical properties 13,21 especially in adult patients. BL can increase the pressure on joint contacts, 44 limiting limb mobility or producing significant histological changes in joint tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors must be taken into consideration when attempting to mitigate the risk of flap loss, with one of which being rate of bone transport. While Jupiter et al [62] concluded that the free tissue and the native tissue undergo equal amounts of stretch and lengthening, Horas et al [103] noted a difference in speed between bone transport and soft-tissue movement, which could potentially jeopardize the vascular pedicle secondary. This risk increases with the amount of transport needed.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, bone transport trusts on the long-standing distraction osteogenesis to gradually move an osteotomized surrounded bony fragment towards the position of the original defect while simultaneously forming a bone callus on the other side, the docking site [2][3][4]. However, this regeneration process carries inherent risks, particularly concerning viscoelastic and structural alterations in the neighboring soft tissues (e.g., skin, tendons, or muscles) [5][6][7][8]. Another traditional solution lies in incorporating autogenic and allogenic bone grafts to encourage cell regenerative activity in the gap, mainly vascularized free fibular or Papineau open cancellous bone grafting [9][10][11].…”
Section: Introductionmentioning
confidence: 99%